Los que se van: texto de vanguardia (Crítica) - Gómez, Facundo (2015)
Ecuadorian literature of the 1930s has been read repeatedly through a strict dichotomy that adamantly separates avant-garde works and those associated with social realism. On the opposition between the rhetoric of Pablo Palacio and Jorge Icaza, criticism has placed the works of the period in a Manichean scheme that precludes consideration and the immanent study of certain texts with heterogeneous features, such as volume stories Los que se van written by Demetrio Aguilera Malta, Enrique Gil Gilbert and Joaquín Gallegos Lara in 1930. Although read as landmark in the literature of social argument, the text combines the motivations and resources of the two inflections mentioned. The analysis of their aesthetic procedures, such as assembly, ellipsis and the particular use of language bring the text closer to the attempt of a sector of Latin American art that combined the experimentation of literary forms with an eloquent intention of representation and complaint.